2021
DOI: 10.1016/j.jaad.2020.09.074
|View full text |Cite
|
Sign up to set email alerts
|

Occupational dermatitis to facial personal protective equipment in health care workers: A systematic review

Abstract: Background Prolonged wear of facial protective equipment can lead to occupational dermatoses. Objective To identify important causes of occupational dermatoses from facial protective equipment. Methods A systematic review following PRISMA guidelines was performed using PubMed and Embase databases. Articles were included if they reported occupational dermatoses caused by surgical/procedure masks and/or N95 respirators. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
91
2
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(102 citation statements)
references
References 22 publications
2
91
2
7
Order By: Relevance
“…HCW in the present study wore face masks for longer periods of time due to their professional duties, therefore facilitating the occurrence of itch and eventually leading to mask touching. Other possible causes of the latter include discomfort associated with mask wearing, exacerbation of pre-existing acne, occupational dermatitis, seborrheic dermatitis or rosacea [ 23 , 24 , 25 , 26 ]. Nonetheless, certain studies demonstrated that wearing face masks tends to decrease face touching behaviors, both in the general public [ 27 , 28 ] and also in HCW [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…HCW in the present study wore face masks for longer periods of time due to their professional duties, therefore facilitating the occurrence of itch and eventually leading to mask touching. Other possible causes of the latter include discomfort associated with mask wearing, exacerbation of pre-existing acne, occupational dermatitis, seborrheic dermatitis or rosacea [ 23 , 24 , 25 , 26 ]. Nonetheless, certain studies demonstrated that wearing face masks tends to decrease face touching behaviors, both in the general public [ 27 , 28 ] and also in HCW [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…O autor ressalta que esse fato pode ser devido já ter tido intervenção dos gestores, ou omissão por medo. Mediante a uma situação de pandemia, em que toda a equipe está à frente de novas diretrizes e normas, as instituições devem garantir a segurança dos funcionários a partir do repasse de instruções à equipe, treinamentos para evitar o uso incorreto ou inapropriado, sendo a comunicação crucial para o atual momento 18 . Cabe então aos gestores a responsabilidade pelo êxito no repasse de informações necessárias à equipe, agindo de forma preventiva contra os danos causados por uma pandemia inesperada.…”
Section: Discussionunclassified
“… 11 ACD is a biphasic type IV delayed type hypersensitivity reaction that develops in response to contact allergens such as preservatives (formaldehyde), dyes (disperse blue), and metals (nickel). 12 Acute episodes of ACD can present with edema, erythema, and vesiculation. 11 Chronic ACD can lead to lichenification and fissuring of the skin.…”
Section: Common Types Of Occupational Dermatitismentioning
confidence: 99%
“… 11 ICD occurs from direct cytotoxic injury to the skin induced by a physical or chemical irritant. 12 ICD may include ulcerations and fissuring at the affected site, 12 with symptoms of pruritis and burning sensation occurring immediately after exposure. 11 ICD has been reported as a result of prolonged wearing of PPE and rigorous and frequent hand washing in the setting of COVID-19 (see Table 2 ).…”
Section: Common Types Of Occupational Dermatitismentioning
confidence: 99%